Smart Cities and Positive Energy Districts Urban Perspectives in 2021 - Maestosi, Paola Clerici (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book Smart Cities and Positive Energy Districts: Urban Perspectives in 2020 is the second book published by MDPI on the topic. It highlights the most recent internationally/nationally funded projects on Smart Cities and Positive Energy Districts, providing readers with an overview of the most recent and effective solutions to support the transition of urban areas towards climate neutrality as well as inspiring solutions not only for researchers but for local governments who seek to transform urban areas into sustainable places.